PENGEMBANGAN MULTIMEDIA INTERAKTIF BERMUATAN SOAL-SOAL HOTS BERBANTUAN SOFTWARE ARTICULATE STORYLINE PADA MATERI MATRIKS KELAS XI - ulya dina; sunismi sunismi; eryk yayan (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The purpose of this research is to produce interactive multimedia containing HOTS questions assisted by articulate storyline software in class XI matrix material. This interactive multimedia development uses the ADDIE development model which includes 5 stages, namely analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). The subjects in this study were material experts, design experts, media experts, as well as 4 expert practitioners and 10 users/users from 2 schools, namely SMA NU Pakis and SMK Ma'arif NU Pakis. The aim is to determine the validity of the product and the practicality of the product produced. The data analysis used is quantitative and qualitative. According to the assessment of material experts, design and media experts, the average was 3.35; 3.82; and 3.1 with an overall average of 3.42. Meanwhile for the results of 4 expert practitioners obtained an overall average of 3.49. While the user trial involving 10 students of class XI, obtained an overall average of 3.2. So it can be concluded that interactive multimedia containing HOTS questions assisted by articulate storyline software in class XI matrix material is declared feasible and can be used in the learning process.Keywords: Development, interactive multimedia, HOTS, software, articulate storyline, matrixÂ